Fertility Investigations and taxonomy of the Soils of Regional Agricultural research Station, Pattambi - Deepa K P (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1995)
The Regional Agricultural Research Station, Pattambi has entered it seventh decade of activities. The total area of the station is 63.64 ha and it includes both upland and low land. A detailed survey of the soil in the area of the station has not been made by the Soil Survey Department and hence a taxonomic classification of the soil and fixing of the soil serious as per the soil taxonomy has not been done so far. Therefore the present study was formulated to find out of the morphological and Physico-chemical characteristics of soil profiles of selected blocks, to analyse the surface soil samples from all the blocks for fertility parameters, to classify the soils under taxonomy and to prepare the soil fertility map of the station. The soils had predominantly red hues. Good structural development was noticed in all soils except in ill drained areas. Coarse fragments formed a predominant part in the soil samples collected. In general the soils were acidic in nature. Organic carbon content was low irrespective of crops grown. The nitrogen content of all soils were also low. No regular pattern of distribution with depth was obtained for total reserves of N, P2 O5, K2 O, CaO, MgO and Na2O which were low. Total Fe2 O3 content was fairly high. The cation exchange capacity calculated by NH4 OAC method was low for all the soils. Among the exchangeable bases, Ca formed the predominant cation. With regard to the available nutrient content of soils, nitrogen status of the soul worked out based on the organic carbon content showed that it was high in C block, low in blocks I and IX and medium in the remaining 19 blocks. Nutrient index worked out for available P content showed that it was medium in 12 blocks i.e., E, M, K, I, II, III, IV, V, VI, VII, IX, X and high in the remaining 10 blocks. For available K, the nutrient index values indicated that it was low in 10 blocks and medium in 12 blocks. Based on the nutrient indices, the fertility map of the station was prepared. Based on the profile soil sample analysis, classification of the soils under soil Taxonomy was attempted upto the subgroup level. Among the nine profiles, only 3 i.e., F, I and V fell under Inceptisols and the remaining 6 i.e., F, I and V fell under Inceptisols and the remaining 6 i.e., B, C, I, VIII, IX and X were under Entisols.